(untitled) (Bulletin of Innovative Research, 2026)
The article examines the problems of artistic expression in the short stories of the Uzbek writer Nurali Kabul and the Abkhaz-Russian writer Fazil Iskander. It analyzes the specific features of the authors’ artistic thinking, their approaches to depicting human beings and reality, as well as the peculiarities of narrative structure. Special attention is paid to the role of national color, the author’s position, and the system of images in shaping the artistic world of the works. The comparative analysis makes it possible to identify both general patterns of artistic interpretation of reality and the individual characteristics of each writer’s creative method.